Negro Employment in the Maritime Industries : a Study of Racial Policies in the Shipbuilding, Longshore, and Offshore Maritime Industry - Rubin, Lester; Northrup, Herbert R. (Herbert Roof), 1918-2007; Swift, William S. (Recent Industrial Research Unit Studies, 1974)
This book is a volume in the Penn Press Anniversary Collection. To mark its 125th anniversary in 2015, the University of Pennsylvania Press rereleased more than 1,100 titles from Penn Press's distinguished backlist from 1899-1999 that had fallen out of print. Spanning an entire century, the Anniversary Collection offers peer-reviewed scholarship in a wide range of subject areas.